Interworking of mans and ATM based B-ISDN / Siti Aminah Khasiman - Khasiman, Siti Aminah (1997)
This paper examines the interworking of distributed queue dual bus (DQDB) metropolitan area network (MAN) with the asynchronous transfer mode (ATM) of BISDN. We will also investigate the relationship between MAN and ATM and how MANs can integrate with ATM based B-ISDN. This includes a comparison and discussion of the interworking of DQDB MAN and B-ISDN on the interworking of services. There are 3 stages how we can implement this project. The first stage is to analyse the operation of DQDB MAN, followed by the second stage, that is the operation of ATM and the last stage, that is the interworking between of MAN and ATM network. For this project, we will focus on the DQDB operation. This due to DQDB model with multipriority traffic using simulation packet NETWORK 11.5 in developing the network. The characteristic and the performance of the network is analysed using the simulation results. This include, discussions on analysing the performance evaluation of DQDB model with respect to their cell delay, heavy traffic, under traffic, maximum queue length and channel utilisation.